An analogue of Bernside’s lemma for finite inverse symmetric semigroup - Voloshyna, T.V. (Carpathian Mathematical Publications, 2010)
An analogue of Bernside's lemma for transitive permutation representations of finite inverse symmetric semigroup is obtained.